Location and Agglomeration: The Distribution of Retail and Food Businesses in Dense Urban Environments - Sevtsuk, Andres (Journal of planning education and research, 2014)
This article analyzes location patterns of retail and food establishments, whose presence constitutes an important aspect of livable and walkable neighborhoods. Using approximately fourteen thousand buildings on the street network of Cambridge and Somerville, Massachusetts, as units of analysis, this article tests five hypotheses about retail locations found in previous literature and estimates the impacts of different location characteristics for all retail and food-service establishment as a group and for different store categories individually. The results describe how specific location attributes impact the probabilities of finding retailers, which can inform the planning of commercial activity clusters.